Inclusive Business and Its Contribution to Employing People with Disabilities - Felix*, Antonius; Wijaya, Felix Jonathan; Venita, Erin; Melisa, Melisa; Patricia, Angel; Sidarta, Eric; Athaliav, Tania (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
The purpose of this research is to investigate how Kopi Sunyi's unique approach to inclusive employment and education influences customer perceptions and fosters inclusivity. Utilizing a comprehensive research methodology, including analysis of online reviews, direct visits, and observational data, this study offers valuable insights into Kopi Sunyi's role in fostering inclusivity and challenging societal norms. Results reveal that Kopi Sunyi's commitment to providing employment opportunities and inclusive education through the Sunyi Academy program has positively influenced customer perceptions, fostering a welcoming atmosphere and friendly service. The cafe's efforts in challenging societal stigmas have led to increased awareness and support for individuals with disabilities in the workforce. The findings underscore the transformative potential of inclusive business practices in promoting social inclusion and empowerment. Keyword: Workplace Disabilities; Inclusive Environment; Equality in Workplace; Social Inclusion; Job Opportunities